Study on the hierarchical structure of container port systems along the South China Sea in the context of low carbon emissions - Li, Yan; Wu, Zongnan; Sun, Liang; Yue, Jiafei (Frontiers in Marine Science, 2024)
Under the low-carbon background, 37 ports of countries along the South China Sea with capacity ranking in the world’s top 100 container ports are selected as the research object to establish a shipping network, construct a directed dichotomous shipping network, and divide the port tiers after finding the kernel number by using kernel analysis method, respectively, to explore the relationship between tiers and the relationship between ports at the higher level, and then make clear the direction of the improvement for the reduction of carbon emissions. The results show that: the routes sent between container ports in countries along the South China Sea have formed a more stable connection, but the receiving routes are still in a passive position, and the port call relationship is affected by the port hierarchy. High-level ports such as Shanghai Port and Singapore Port undertake the transshipment function of cargo concentration and redistribution within the network. The small-world characteristics among ports such as Singapore Port, Ningbo Port, Haiphong Port, Shenzhen Port, Guangzhou Port, and Linchaban Port are obvious. Based on the results of the empirical analysis, corresponding suggestions are put forward to optimize the structure of the container port system in the countries along the South China Sea and promote the low-carbon development of the sea.